2020
DOI: 10.2139/ssrn.3754804
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19 Dynamics and the Effects of Interventions in the Philippines: A Mathematical Modelling Study

Abstract: Background: COVID-19 initially caused less severe outbreaks in many low-and middle-income countries (LMIC) compared with many high-income countries, possibly because of differing demographics, socioeconomics, surveillance, and policy responses. Here, we investigate the role of multiple factors on COVID-19 dynamics in the Philippines, a LMIC that has had a relatively severe COVID-19 outbreak. Methods:We applied an age-structured compartmental model that incorporated time-varying mobility, testing, and personal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…The impact of the community quarantines imposed by the government are reflected on the reduction parameter δ and transmission rates β and β F . The estimated 20% reduction in transmission for the behavior-changed class compares with a mathematical model of COVID-19 transmission in the Philippines which showed that the minimum health standards reduced the probability of transmission per contact by 13 − 27% [41]. As the community quarantine was relaxed from Period 1 to 2, the transmission rate of the disease ( β ) increased from Period 1 to 2, while the rate of behavior change or transmission rate of awareness or fear of COVID-19 ( β F ) decreased from Period 1 to 2.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the community quarantines imposed by the government are reflected on the reduction parameter δ and transmission rates β and β F . The estimated 20% reduction in transmission for the behavior-changed class compares with a mathematical model of COVID-19 transmission in the Philippines which showed that the minimum health standards reduced the probability of transmission per contact by 13 − 27% [41]. As the community quarantine was relaxed from Period 1 to 2, the transmission rate of the disease ( β ) increased from Period 1 to 2, while the rate of behavior change or transmission rate of awareness or fear of COVID-19 ( β F ) decreased from Period 1 to 2.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a reflection of various personal protective behaviors or compliance to minimum health standards. Literature indicates a range of α = [0.1, 0.6] [5]; however, the original range of α = [0, 1] [8] is used in the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The application of a similar modelling framework is described elsewhere ( Caldwell et al, 2021 ) and the full model description (including differential equations) is provided in the Supplementary File, with all code publicly available through https://github.com/monash-emu/AuTuMN/. The model consists of a modified susceptible (S)- exposed (E)- infectious (I)- recovered (R) compartment framework.…”
Section: Methodsmentioning
confidence: 99%